PENGEMBANGAN BAHAN AJAR KOMIK PADA MATERI SISTEM TRANSPORTASI MAKHLUK HIDUP UNTUK MENUMBUHKAN MINAT BACA DAN MENINGKATKAN HASIL BELAJAR - Wahab, Abdul; Wasis, Wasis; Indana, Sifak (Universitas Negeri Surabaya, 2016)
One indicator of the success of a learning process IPA is the achievement of learning outcomes of students both competence spiritual, social, knowledge and skills. Many factors make the results of this study are lower among reading of the science lesson is still low and science teaching materials available is insufficient and monotonous. This research aims to produce teaching materials on the comic material transportation system of living things are valid, practical, and effective so as to foster interest in reading and improve learning outcomes. Learning approach used to implement the teaching materials of this comic is the scientific approach as recommended by Curriculum 2013. The development of teaching materials using 4D models and design studies using one group pre-test post-test design. The experiment was conducted on students of class VIII SMPN 1 Sekar Bojonegoro. Data were analyzed using descriptive qualitative. The results of data analysis showed that: (1) a valid teaching materials developed, practical and effective; (2) study carried out by both categories; (3) more active learners in learning; (4) reading learners experiencing growth with a percentage increase of 56.36%; (5) the study of students has increased by a score of N-gain high category. Based on the above results, it can be concluded that the teaching materials have been developed comic valid, practical, and effective way to foster interest in reading and improve the learning outcomes of students. Salah satu indikator keberhasilan suatu proses belajar mengajar IPA adalah tercapainya hasil belajar peserta didik baik kompetensi spiritual, sosial, pengetahuan dan keterampilan. Banyak faktor yang membuat hasil belajar ini rendah di antaranya adalah minat baca terhadap matapelajaran IPA masih rendah dan bahan ajar IPA yang tersedia tidak mencukupi serta bersifat monoton. Penelitian ini bertujuan untuk menghasilkan bahan ajar komik pada materi sistem transportasi makhluk hidup yang valid, praktis, dan efektif sehingga mampu menumbuhkan minat baca dan meningkatkan hasil belajar. Pendekatan pembelajaran yang digunakan untuk menerapkan bahan ajar komik ini adalah pendekatan saintifik sesuai anjuran Kurikulum 2013. Pengembangan bahan ajar menggunakan model 4D dan desain penelitian menggunakan one group pre-test post-test design. Penelitian dilaksanakan pada peserta didik kelas VIII SMP Negeri 1 Sekar Bojonegoro. Teknik analisis data menggunakan deskriptif kualitatif. Hasil analisis data penelitian menunjukkan bahwa: (1) bahan ajar yang dikembangkan valid, praktis dan efektif; (2) pembelajaran terlaksana dengan kategori baik; (3) peserta didik lebih aktif dalam pembelajaran; (4) minat baca peserta didik mengalami pertumbuhan dengan prosentase peningkatan 56,36%; (5) hasil belajar peserta didik mengalami peningkatan dengan skor N-gain berkategori tinggi. Berdasarkan hasil penelitian di atas, dapat disimpulkan bahwa bahan ajar komik yang telah dikembangkan valid, praktis, dan efektif untuk menumbuhkan minat baca dan meningkatkan hasil belajar peserta didik.